Determinación de glucosa en mujeres de la asociación de comerciantes minoristas III Etapa de la Urb. Manuel Arévalo - La Esperanza – Trujillo, 2007.” - Cieza Díaz, Gianina Elizabeth (2008)
The present report was to give know the results obtained of the clinical analysis of blood glucose levels, it was made to130 women of the “Retail Merchants Asosiation’s Manuel Arévalo (ACOMIMAR)”, La Esperanza district, Trujillo city. We used “The Enzymatic Method”, to determinate the concentration of glucose in blood of the patient. The principal objective was to determine and to analyze the concentration of glucose and then give information to the patients of their results, finally orientate them if is necessary for maintain or recover their health. For our results, we used the percentage calculate according to the division for age and Glycaemia presented, our population was divided in: Hypoglicaemia, Normoglycaemia and Hyperglycaemia. We Obtained that: 22,31% of women presented Hipoglycaemia, 57,69% were Normals and 20% presented Hiperglycaemia. According with the biggest percentage of women Hipoglicémicas (26,67%) were patients that their ages oscillated between 18-29 years old, on the other hand the biggest percentage of Hiperglicémicos (31,03%) were 40-49 years old